Determinasi Risiko Audit, Pengalaman Auditor dan Profesionalisme Terhadap Pertimbangan Tingkat Materialitas pada Kantor Akuntan Publik Di Kota Padang - Dewi Zulvia; Siski Tanmela (JURNAL PUNDI, 2022)
The purpose of this study to provide empirical evidence of the effect of audit risk, auditor experience and professionalism on the consideration of the level of materiality at the Public Accounting Firm in the city of Padang. The population in this study are all public accoounting firms in the city of Padang. Purposive sampling technique is the sampling technique used in this study. The sample in this study were all senior auditors and junior auditors at the Public Accounting Firm Padang. This type of research is quantitative research. Multiple linear regression analysis was used in this study The results showed that audit risk did not significantly influence the consideration of materiality level as indicated by a significant value of 0,080, while the auditor’s experience and professionalism had a positive and significant impact on the consideration of materiality level indicated by significant values of 0,000 and 0,000